PEMANFAATAN LIMBAH TONGKOL JAGUNG MELALUI PENAMBAHAN EKSTRAK DAUN KERSEN (Muntingia Calabura) DALAM PEMBUATAN EDIBLE FILM - Rais Nur Latifah; Nurmilatillah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Food is a product that is synonymous with packaging techniques to protect the quality of the food. The packaging technique used edible film. This study aims to make a food protective coating from corn cobs and cherry leaf extract. The research method used the preparation of edible film, functional group analysis with FTIR instrument, mechanical properties analysis, pH testing and antibacterial properties analysis. The results showed that the edible film contains flavonoid compounds with antibacterial activity. The results of the analysis of the identification of functional groups on edible films are the presence of typical absorption of hydroxide groups, C-H groups, carbonyl groups and glycosidic bonds. Analysis of the mechanical properties of edible film for the thickness level is 0.224 mm and the tensile strength is 3.855 N/cm2. Meanwhile, based on pH testing, edible films were at a neutral pH during a 10-day storage period.